Development of near homogeneous properties in wire arc additive manufacturing process for near-net shaped structural component of low-carbon steel. (April 2022) - Paul, Amrit Raj; Mukherjee, Manidipto; Raja, Manivannan; Kundu, Soumyajit; Chatterjee, Avik
Low-carbon steel is a common structural material, but additively manufactured structural component of this material is rare due to its inhomogeneous properties. In this article, the wire arc additive manufacturing method was used to achieve near homogeneous properties of a low-carbon steel structural component. The process heat input was optimised for the desired layer geometry, and then the optimal energy was applied with a time delay to deposit individual layers. The time delay was used to achieve cyclic heating and cooling treatment of deposited layers. The best possible robotic tool path movement with multi point arcing was further adopted in the study to achieve proper thermal distribution across the structural component. The microstructure of layers was dominated by quasi-polygonal ferrite morphology and pearlite precipitation, with little variation in quantity across the component. The hardness profile was almost consistent with the average hardness of ∼176.92 HV. The proof stress slightly increases with decrease in grain size and increase in ferrite/pearlite ratio, however, the overall tensile behaviour is homogeneous with average σ0.2, σu and ε% values of 427.78 MPa, 527.89 MPa and 22.31%, respectively. The quasi-ductile fracture was generally occurred due to void coalescence around larger inclusions. The overall analysis showed that more than 90% of homogeneity was achieved in microstructural and mechanical behaviour of the deposited component.